Implementasi Low Power State Machine pada Sistem Notifikasi Kecelakaan Sepeda Motor - Lutfi Anang Makruf; Eko Setiawan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In this modern era a motorcycle is very common means of transportation to use. With the increasing population of motorcycle users, accidents caused by motorbikes cannot be avoided. In general, accidents cannot be predicted when and where accidents occur. By using an accident notification system on a motorcycle, it will be easier to find out the location of the accident. So that the device does not consume excessive power on a motorcycle battery, it must have a low power mechanism to be able to save power. Low power and state machine mechanisms can be implemented in a prototype system that serves to inform that an accident has occurred by sending a short message containing the location of the accident. In testing the accuracy and functional levels of several components obtained results that are as expected. The MPU6050 sensor has an accuracy of 84.43%, the NEO6M module has an accuracy of 99.99% and the functional module SIM800L can send short messages properly. In testing the low power mechanism can reduce the power consumed by 22.2 mA or 18.8%. The device consumes power of 117.7 mA without using a low power mechanism and consumes power of 95.5 using the low power mechanism.